Basic Techniques in Pediatric Surgery An Operative Manual - Carachi, Robert; Agarwala, Sandeep; Bradnock, Tim J.; Lim Tan, Hock.; Cascio, Salvatore; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This unique manual is a (3z(Bsurgical cookbook(3y (Bdesigned to provide clear and concise guidance for trainees in pediatric surgery. With the aid of simple line drawings depicting each operative step, more than one hundred frequently performed procedures are explained and demonstrated. The reader will learn how to perform each procedure effectively and safely, avoiding potential complications. The full range of surgery is covered, including basic surgical skills, day surgery procedures, emergency surgery procedures and minimally invasive surgery. The book will be of value not only to trainees in pediatric surgery but also to trainees in general surgery, theatre nurses, parents and carers.s
From the content: Basic Surgical Techniques -- The WHO Safe Surgery checklist -- Positioning -- Preparation -- Head and Neck -- Layers of the scalp and suturing -- External and internal angular dermoid -- Cleft lip and palate -- Spine and Limbs -- Spina Bifida -- Forearm manipulation and molded cast -- Distal radius wiring -- Thoracic -- Chest drain insertion -- Thoracotomy -- Abdomen -- Upper GI Endoscopy -- The endoscopic management of upper GI bleeding -- Proctoscopy and flexible sigmoidoscopy -- Groin and Genitalia -- Exposure of the inguinal canal and Spermatic Cord Structures -- Inguinal hernia and ligation of patent processus vaginalis -- Incarcerated inguinal hernia -- Urology -- Cystourethroscopy -- Urethral and suprapubic catheterisation -- Open surgical approaches to the kidney -- Perineum -- Anal fissures and skin tags -- Perianal abscess and fistula-in-ano -- Minimally Invasive Surgery -- Ergonomics, Heuristics and Cognitive Skills in Laparoscopic Surgery -- Complications of laparoscopic surgery.
Keywords: Medicine; Abdomen -- Surgery; Surgery; Thoracic surgery; Trauma; Urology; Medicine & Public Health; Pediatric Surgery; Pediatric Surgery; Abdominal Surgery; Thoracic Surgery; Traumatic Surgery; Urology/Andrology.